BIDDING FOR THE EUROPEAN CAPITAL OF CULTURE: COMMON STRENGTHS AND WEAKNESSES AT THE PRE-SELECTION STAGE - Nechita, Florin (My University, 2015)
This article explores the common strengths and weaknesses, as they are revealed by the pre-selection reports issued after Selection Panels analyses the applications of the cities competing for the European Capital of Culture (ECOC) title. The results of the content analysis of the 11 pre-selection reports that cover the years 2013 to 2019 of the ECOC title could add a new interpretation to the guides for cities preparing to bid and concentrates directions for future research on successful bidding approaches.
Keywords: European Capital of Culture; community engagement; European dimension; bidding strategies